Mapping modern Mahayana : Chinese Buddhism and migration in the age of global modernity - Reinke, Jens. (Berlin ; Boston : Walter de Gruyter GmbH, 2021)
This book presents a multi-sited ethnographic study of the global development of the Taiwanese Buddhist order Fo Guang Shan. It explores the order's modern Buddhist social engagements by examining three globally dispersed field sites: Los Angeles in the United States of America, Bronkhorstspruit in South Africa, and Yixing in the People's Republic of China. The data collected at these field sites is embedded within the context of broader theoretical discussions on Buddhism, modernity, globalization, and the nation-state. By examining how one particular modern Buddhist religiosity that developed in a specific place moves into a global context, the book provides a fresh view of what constitutes both modern and contemporary Buddhism while also exploring the social, cultural, and religious fabrics that underlie the spatial configurations of globalization.
Keywords: Fo Guang Shan Buddhist Order; Buddhism -- Social aspects -- China -- Yixing Shi; Buddhism -- Social aspects -- California -- Los Angeles; Buddhism -- Social aspects -- South Africa -- Bronkhorstspruit